Three-dimensional printing of zirconia: characterization of early stage material properties. Issue 1 (20th December 2019) - Suominen, Jussi M.; Frankberg, Erkka J.; Vallittu, Pekka K.; Levänen, Erkki; Vihinen, Jorma; Vastamäki, Teemu; Kari, Risto; Lassila, Lippo V. J.
Abstract: Objective: The aim of this study was to evaluate the mechanical properties of 3D printed zirconia (ZrO2 ).  Materials and Methods: The test specimens were produced with a 3D printer that uses lithography-based ceramic manufacturing (LCM) technique with two different parameters in horizontal and vertical printing orientations. Altogether four groups of nine specimens were printed and examined. Mechanical characterization was performed using 3-point bending test (ISO 10477) and surface microhardness (Vickers) test. Grain structure, porosity and printing layer morphology were examined with optical and scanning electron microscopy (SEM). Additionally fractography analysis was done to investigate and evaluate features of fracture initiation site. Numeric results were statistically analyzed with ANOVA ( a  = 0.05). Results : The average flexural strength reached for printed zirconia was 499 MPa (+/−75 MPa) for specimens printed in horizontal orientation and 575 MPa (+/−69 MPa) for specimens printed in vertical orientation. Optical microscopy and SEM analysis revealed that fractures initiated between the printing layers or from a local porosity. Printing layer thickness varied from under 13 μm to over 20 μm. Conclusions : The study revealed that 3D printed zirconia has challenges in regards to layer integration. Based on this study, 3D printed zirconia still suffers from low mechanical strength, which together with long carbon-debinding time, does not make 3D printed zirconia a potential material for dental appliances at this stage. Further research is needed to create more suitable zirconia precursor slurries and to optimize printing parameters and sintering conditions to be able to 3D print zirconia with higher mechanical properties.